The effect of early fusion of the spheno-occipital synchondrosis on midface hypoplasia and obstructive sleep apnea in patients with Crouzon syndrome. Issue 7 (July 2017) - Driessen, Caroline; Rijken, Bianca F.; Doerga, Priya N.; Dremmen, Marjolein H.; Joosten, Koen F.; Mathijssen, Irene M.
Abstract: Introduction: The investigators hypothesized that patients with Crouzon syndrome and premature fusion of the spheno-occipital synchondrosis (SOS) more often have, or have more severe midface hypoplasia and obstructive sleep apnea (OSA). Methods: A prospective cohort study was performed among patients with Crouzon syndrome to analyze SOS closure, midface hypoplasia represented by the sella-nasion angle (SNA) and OSA. Results: Forty patients were included in whom the OSA-prevalence was 65%. Kaplan Meier analyses suggest a trend towards earlier closure of synchondrosis in patients with OSA (p = 0.066). The mean SNA was 74.7°. There was a positive effect of age on the SNA (p = 0.020). There was no difference in SNA for patients with an open SOS as compared to patients with a closed SOS after correction for age. Conclusions: The longitudinal data are suggestive of a trend towards earlier fusion of the SOS in patients with Crouzon syndrome and OSA as compared to patients with Crouzon syndrome without OSA. Although the SNA increases with age, our results suggest that this increase in independent closure of the SOS.